2020
DOI: 10.1021/acs.energyfuels.0c03338
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis on Gas and Solid Residues of Pre- and Post-explosion Coal Dust

Abstract: The gas and solid residues after coal explosion contain abundant information that can reflect the reaction mechanism and hazardous effects of coal dust explosion. To investigate the characteristics of gas and solid products of coal dust explosion, experiments were conducted in a 20 L spherical explosion vessel. The micromorphology characteristics and chemical functional groups of solid residues were observed by scanning electron microscopy and Fourier-transform infrared (FTIR) spectroscopy analysis. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Successful experiments with gas detonation engines have provided valuable insights applicable to harnessing coal dust explosions. 15 A significant body of research has been conducted on the macroscopic explosive properties 16,17 and microstructure 18,19 of pulverized coal, which provides a theoretical foundation for the development and application of pulverized coal explosive engines. A proposed clean power plant, constructed in situ, comprises three functional units: a coal mine system, a detonation power generation system, and a transmission system, as illustrated in Figure 6.…”
Section: Clean Power Plantsmentioning
confidence: 99%
“…Successful experiments with gas detonation engines have provided valuable insights applicable to harnessing coal dust explosions. 15 A significant body of research has been conducted on the macroscopic explosive properties 16,17 and microstructure 18,19 of pulverized coal, which provides a theoretical foundation for the development and application of pulverized coal explosive engines. A proposed clean power plant, constructed in situ, comprises three functional units: a coal mine system, a detonation power generation system, and a transmission system, as illustrated in Figure 6.…”
Section: Clean Power Plantsmentioning
confidence: 99%
“…where ω (Hz) corresponds to the angular frequency, f (Hz) is the frequency of the electric field, τ w (s) is the relaxation time of water polarization, ε w0 (F/m) is the dielectric constant of water in an electrostatic field, ε w∞ = 4:9 F/m represents the dielectric constant at high frequency, ε 0 = 8:854 * 10 −12 F/m is the dielectric constant of vacuum, and б (S/m) is the conductivity of water. Equation (5) indicates that the relaxation time τ w of the polarization of water media in the microwave field and the dielectric constant ε w0 of water in the electrostatic field are 7 Geofluids important parameters that affect the dielectric loss of water. They are functions of temperature, as seen in equations ( 6) and ( 7), as shown in Figures 6(a Conductivity б, which is closely related to the ion concentration of the solution, is the most important parameter that affects Joule heat loss.…”
Section: Effect Of Ion Concentration On Dielectric Properties Ofmentioning
confidence: 99%
“…In coal underground mineral deposits, the working faces gradually shift to the deeper part of the formation as mining opera-tions progress to deeper levels. Also, coal and gas explosions may cause serious injuries to the personnel [5], events that are especially catastrophic [6]. In coal mines, gas has become an important factor restricting the efficiency of mining activities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment of explosion under conditions with different air-fuel ratios, Lin et al [23] suggested that the volume fraction of flammable gas in residual gases of CH 4 /coal dust/air mixture explosions is higher than that of CH 4 /air mixtures. Nie et al [24] investigated the characteristics of gas and solid products of coal dust explosion in a 20 l spherical explosion vessel.…”
Section: Introductionmentioning
confidence: 99%